The Influence of Brand Image and Perceived Quality on Customer Loyalty at Merlin Gold Shop in Bandar Lampung - Devi Mala Dewi; Wenny Permata Sari (Universitas Dehasen Bengkulu, 2026)
Competition in the jewelry industry requires business actors to build and maintain consumer loyalty through strengthening brand image and quality perception. Merlin Gold Shop Bandar Lampung as a relatively new business still faces challenges in maintaining consumer loyalty amid competition with established gold stores. This study aims to evaluate the impact of quality perception and brand image on consumer loyalty at Merlin Gold Store in Bandar Lampung. This study uses a causal associative approach with a quantitative methodology. Questionnaires were distributed to 100 respondents, and data were collected through multiple linear regression analysis with IBM SPSS Statistics version 27. Research shows that consumer loyalty is strongly influenced positively by the perception of quality and brand image. Simultaneously, consumer loyalty has been shown to be significantly influenced by the perception of quality and brand image. These results show that consumer trust and satisfaction can be improved with a strong brand image and perceived high-quality products. The study's conclusions reinforce the idea that local gold stores should implement important strategies to grow and maintain consumer loyalty, including consistently improving product quality and strengthening brand image.